UJI AKTIVITAS EKSTRAK KULIT BATANG MANGGA ARUMANIS (Mangifera indica L) SEBAGAI ANTIHIPERTENSI PADA TIKUS PUTIH JANTAN DIINDUKSI NaCl 5% - Ifmaily Ifmaily; Irwandi Irwandi; Siti Hajir; Aprilia Aprilia (Sekolah Tinggi Pariwisata Mataram, 2022)
The part of arumanis mango plant (Mangifera indica L) is growing in Indonesia, a plant that has the potential to be a herbal medicinal plant because it contains secondary metabolites, one of which is a flavonoid which is useful as an antihypertensive. The purpose of this study was to determine whether the stembark extract of mango arummanis (Mangifera indica L) could affect blood pressure in hypertensive white male rats and to determine the variation in dosage of arummanis mango stembark extract (Mangifera indica L) which had an antihypertensive effect on hypertensive white male rats. In these research there was 24 white male rats was divided 6 groups insist of negative control, positive control, dosages groups ( 60, 120, 180 ) mg/kgBW and comparison group (Captopril 25 mg). Inducer was NaCl 5 %. Blood pressure measurements were performed using the (Non Invasive Blood Pressure) NIBP CODA tool. Data analysis used one-way ANOVA followed by the Duncan test, and the results showed that there were significant differences in systolic and diastolic blood pressure in the test group with (p<0.05). In conclusion, the extract of arummanis mango stembark (Mangifera indica L) can affect blood pressure in hypertensive white male rats with the best effect of antihypertensive at a dose of 180 mg /kgBW.